A comparative study on quality of life and sexual function after vaginal delivery and Cesarean section - Mehrnaz Valadan; Mamak Shariat; Zahra Rezaei; Fedyeh Hagholahi; Golnaz Sheikholeslami; Pouya Bandegi (Tehran University of Medical Sciences, 2015)
Background & Aim: Many changes occur during and after pregnancy which affect physical, psychological and social health and generally women's quality of life. This study aims to explore the relationship between quality of life and sexual dysfunction after delivery. Methods & Materials: This cohort study was designed to compare the relation of mode of delivery to quality of life and sexual satisfaction in 330 pregnant women referred to hospitals of Tehran University of Medical Sciences. Sexual function questionnaire including 20 questions and quality of life questionnaire including 26 questions were developed based on Female Sexual Function Index (FSFI) and World Health  Organization life quality (WHOQOL- BREF) questionnaire,  respectively. Data were analyzed through SPSS version 15 software using descriptive and analytical methods (t-test, X2 test, Fisher's exact test and analysis of variance). Results: The mean sexual function score in the vaginal delivery and Cesarean section groups were 45.25±5.59 and 45.50±6.03, respectively, which shows no significant difference. No significant difference was seen regarding the mean score of quality of life between vaginal delivery group (87.8±10.70) and Cesarean section group (88.25±11.29). Also no significant difference was seen between two groups of study, considering different aspects of life (physical, psychological, environmental and social). Conclusion: Quality of life was similar in both groups of vaginal delivery and Cesarean section. Therefore, authorities in charge of health programs can have a leading role in changing people's concept of delivery and developing a positive attitude towards vaginal delivery. This could be achieved through effective public training schedules.